Immunogenicity of COVID-19 vaccination in kidney transplant recipients - V S Jibia; Chelvamalai Muthukumaran; Shivakumar Dakshinamoorthy; Vaishanavi Devi Rajarathinam; Guhan Senthilkumaran; Premkumar Devaraju; Vinoj Murugesan; Venkatesh Arumugam; Tanuj Moses Lamech; Sakthirajan Ramanathan; Srinivasaraman Govindarajan; Natarajan Gopalakrishnan (Indian Journal of Transplantation, 2023)
Context: Kidney transplant recipients (KTRs) represent a high-risk population but were grossly underrepresented in COVID-19 vaccination trials. Aims: The aim was to study the immunogenicity of two COVID-19 vaccines (Covaxin and Covishield) among KTRs. Subjects and Methods: We conducted a prospective observational study among KTRs who consented to receive two doses of the COVID-19 vaccine – either Covaxin or Covishield. Patients who underwent kidney transplant during the previous 6 months or had received antirejection therapy during the previous 1 month were excluded from the study. Antibody titers to the spike protein of COVID-19 were measured at baseline and at 4 weeks after the second dose of the vaccine. Statistical Analysis: A univariate analysis was performed in the subgroup of patients who were seronegative at baseline, to identify factors that were associated with seroconversion. The Chi-square test or the Fisher's exact test was used to compare categorical variables, and the Mann–Whitney U-test was used to compare continuous variables. P < 0.05 was considered statistically significant. Results: A total of 150 KTRs were studied, of whom 98 received Covaxin and 52 received Covishield. At baseline, even before vaccination, 63.3% of patients (n = 95) were found to be seropositive. Among those who were seronegative (n = 55) at baseline, seroconversion was noted in 34.5% of patients (n = 19), of which 15.7% (n = 3) had a robust response with antibody titers >250 U/mL. Conclusions: Among KTRs who were seronegative at baseline, a seroconversion rate of 34.5% was demonstrated after two doses of Covaxin or Covishield.